2021
DOI: 10.4103/jehp.jehp_837_20
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of families raising autistic children

Abstract: BACKGROUND: Conditions and needs of autistic children have impacts on both the children and the family members who have crucial roles in raising the child. The prevalence of autism is increasing, and this fact makes it necessary to focus more on experiences of parents who have children with autism spectrum disorder (ASD). Hence, this study aimed to reflect the experiences of parents who have autistic children. MATERIALS AND METHODS: The present study was a qualitative r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Iranian parents of children with ASD experience depression at various stages, including after diagnosis, after realizing that the disorder is incurable, and after ineffective treatment measures. Anxiety is another psychological problem expressed by parents ( 20 , 22 , 25 , 26 , 28 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Iranian parents of children with ASD experience depression at various stages, including after diagnosis, after realizing that the disorder is incurable, and after ineffective treatment measures. Anxiety is another psychological problem expressed by parents ( 20 , 22 , 25 , 26 , 28 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Public misbehavior in society causes parents of children with autism to experience different types of stigmas. Isolation, feelings of shame, and pity are other consequences of inappropriate behaviors in society toward these children and their families ( 14 , 19 , 20 , 22 , 25 , 27 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents of children with autism are imposed with higher health costs than parents of children with other disabilities (8). Studies have shown that treatment costs for children with ASD are three times higher than that for normal children at the same age, as well as that for children with other mental and physical disabilities (17).…”
Section: Discussionmentioning
confidence: 99%
“…The term autism is used for a wide range of problems related to social skills, repetitive behaviors, speech challenges, and nonverbal communication. [ 1 ] Studies on the prevalence of this disorder in recent years show an upward trend. [ 2 3 4 5 ] Regardless of the reasons behind this increasing trend (expanding diagnostic criteria, raising awareness about the disorder, and better diagnosis) being diagnosed with autism spectrum disorder (ASD) can have several negative effects on different aspects of the life of a person with ASD and their family and community.…”
Section: Introductionmentioning
confidence: 99%